1995
DOI: 10.1111/j.1399-6576.1995.tb04112.x
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary sympathetic denervation does not increase airway resistance in patients with chronic obstructive pulmonary disease (COPD)

Abstract: Whether or not neural blockade of pulmonary sympathetic innervation is of relevance for airway resistance in patients with chronic obstructive pulmonary disease (COPD) is unknown. Accordingly we evaluated airway resistance during sympathetic blockade by high thoracic epidural anaesthesia in patients with COPD. Before and 45 min after thoracic epidural injection of bupivacaine 0.75% (6-8 ml; n = 10) total respiratory resistance (oscillometry, ROS), vital capacity (VC), forced expiratory vital capacity in 1 s (F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 21 publications
1
4
0
1
Order By: Relevance
“…This contrasts with our findings which demonstrated that the blockade of neural sympathetic outflow by epidural anaesthesia was not relevant to peripheral airway resistance, neither at rest nor during a bronchoconstrictive challenge in dogs. A similar finding that high thoracic epidural anaesthesia did not alter airway resistance was also demonstrated in patients with bronchial hyper-reactivity (9). Several possibilities may account for our results.…”
Section: Discussionsupporting
confidence: 89%
“…This contrasts with our findings which demonstrated that the blockade of neural sympathetic outflow by epidural anaesthesia was not relevant to peripheral airway resistance, neither at rest nor during a bronchoconstrictive challenge in dogs. A similar finding that high thoracic epidural anaesthesia did not alter airway resistance was also demonstrated in patients with bronchial hyper-reactivity (9). Several possibilities may account for our results.…”
Section: Discussionsupporting
confidence: 89%
“…However, in most other species including humans, non‐cholinergic parasympathetic nerves subserve a primary role in mediating airway smooth muscle relaxation. In fact, although sympathetic‐adrenergic innervation has been clearly demonstrated in human pulmonary arteries and circumstantial evidence suggests that adrenergic nerves also innervate the airway smooth muscle and glands of human airways and lungs (Gothert & Hentrich, 1985; Davis & Kannan, 1987; Pack et al 1988; Martinez et al 1995), the β‐adrenoceptor antagonist propranolol and/or high thoracic epidural anaesthesia has little or no effect on resting airway mechanics and no effect on airways responsiveness to constricting stimuli in healthy human subjects (Laitinen et al 1976; Habib et al 1979; Sterk et al 1985; Groeben et al 1994, 1995). Propranolol is also without effect on nerve‐mediated responses evoked in vitro in human and non‐human primate airway preparations (Richardson & Beland, 1976; Middendorf & Russell, 1980; Canning & Fischer, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that parasympathetic activity is a dominant reversible component of airway obstruction. Groeben et al (1995) detected that the sympathetic blockage induced by high thoracic epidural anesthesia did not cause any evident increase in airway resistance in COPD patients. Primary neural control of airway function is via parasympathetic pathways (Bleecker 1986) and there is no convincing data for the presence of abnormal adrenergic control in the airways of patients with COPD (de Jongste et al 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Although the airway smooth muscle cell possesses many relaxing beta-2 receptors, it receives only a few sympathetic nerves (Davis and Kannan 1987). It was also shown that pulmonary sympathetic denervation by high thoracic epidural anesthesia did not increase airway resistance in patients with COPD (Groeben et al 1995). Inflammation and oxidative stress seem to be more important mechanisms in the pathogenesis of COPD (Ichinose 2003).…”
Section: © 2005 Tohoku University Medical Pressmentioning
confidence: 99%